Muli-UWB Antenna System Design for 5G Wireless Applications with Diversity. (9th June 2021) - Daghari, Marwa; Essid, Chaker; Sakli, Hedi
Abstract : In this paper, we propose a compact Multiple Input Multiple Output (MIMO) antenna system with high isolation for wireless applications in 5G connected devices. This MIMO antenna system with the size of 92 × 88   m m 2 consists of two elliptical antennas symmetrically arranged next to each other. Two decoupling methods which are neutralization and Defected Ground Structure (DGS) are applied to ensure diversity of the proposed MIMO antenna. The single and MIMO antennas are simulated and analyzed then fabricated and measured. A good agreement between measurements and simulations is obtained. These configurations, dedicated to covering the 3.4 GHz band -3.8 GHz, have shown very satisfactory performances more than -30 dB in terms of reduction of mutual coupling between the antennas constituting our system. MIMO diversity parameters, such as Envelope Correlation (ECC), Diversity Gain (DG), and total efficiency, are also studied for each proposed MIMO system. Thus, results demonstrate that our two proposed antenna configurations are very suitable for 5G MIMO applications.